MEAT PRODUCTIVITY OF KHARKIV INBRED LAMBS OF THE PREKOS BREED BORN AS SINGLES AND AS TWINS - Igor KORKH; Nataliya BOYKO; Andriy PALIY; Anatoliy PALIY; Yurii KOVALCHUK; Julia NEGREBA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Studies of meat productivity and meat quality of lambs, taking into account the type of their birth, are relevant for the theoretical justification of the young lamb production issue. The aim of the work was to investigate the meat productivity of lambs taking into account their type of birth. The work was carried out following the Program of Research of the National Academy of Agrarian Sciences 32, "Selection and technological system of transformation of sheep breeding production directions in Ukraine". Kharkiv inbred lambs of the Prekos breed were the object of the study. The lambs were born as singles and as twins. Meat productivity was studied by conducting a control slaughter of 9-month-old lambs, three animals from each group. It has been established that the type of birth of single lambs ensured a reliable increase in pre-slaughter live weight by 13.4 and 19.4%, fresh carcass weight by 11.8 and 19.8%, slaughter weight by 14.0 and 22.2%, with a simultaneous increase in the absolute content of the first class pieces - by 13.1 and 23.5%, the content of pulp - by 24.8 and 30.8%, compared to lambs born among identical and different-sex twins. On the other hand, the muscle tissue of same-sex twins, compared to yearlings born as singles and among twins of different sexes, in terms of the amount of food components accumulated in the dry matter, is characterized by a higher mass fraction of fat - by 8.5 and 10.4%, and ash - by 0.63 and 0.83% and has a higher caloric value - by 38.2 and 43.3%.